Urgensi Pendidikan Humanis Religius Pada Pendidikan Dasar Islam - Agus Riyan Oktori (AR-RIAYAH : Jurnal Pendidikan Dasar, 2019)
Education does not merely promote cognitive intelligence as a person's priority to be accepted in society. The development of all children's potential is the duty of every educator to be able to create a generation that has religious and humanist values. The existence of the concept of humanizing humans need to be introduced from the first time they go through the education process, in order to present a learning process that actually opens a space for children to become creative and imaginative, and to develop their abilities optimally. Throwing away the words that weaken students and assuming them that they have failed in undergoing the educational process becomes an important point of the concept of religious and humanist education. If the education process does not try to emphasize that children are the best masterpieces of educators, children need fun learning methods, children do not get discriminatory behavior from educators, then it will be very likely that the time will bring education to a much better change going forward. In particular, Islamic basic education is a meaningful requirement of the concept of religious and humanist education.